2013
DOI: 10.3109/15569527.2013.834498
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio as a measure of systemic inflammation in psoriasis

Abstract: Our data show that the N/L ratio to be a simple, inexpensive and easily assessable marker of systemic inflammation in patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
96
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 24 publications
14
96
1
4
Order By: Relevance
“…Imtiaz et al (25) showed that NLR was significantly higher in subjects with DM and hypertension compared to the normal population. It has been reported that NLR can be affected in subjects with systemic diseases other than DM or hypertension, like pulmonary hypertension or obstructive sleep apnea syndrome and psoriasis (26)(27)(28). One drawback of our study is that we could not evaluate the existence of other systemic diseases as our study was retrospective.…”
Section: Discussionmentioning
confidence: 82%
“…Imtiaz et al (25) showed that NLR was significantly higher in subjects with DM and hypertension compared to the normal population. It has been reported that NLR can be affected in subjects with systemic diseases other than DM or hypertension, like pulmonary hypertension or obstructive sleep apnea syndrome and psoriasis (26)(27)(28). One drawback of our study is that we could not evaluate the existence of other systemic diseases as our study was retrospective.…”
Section: Discussionmentioning
confidence: 82%
“…Again, numerous studies suggested that NLR is an important criterion in making diagnostic and prognostic decisions in psoriasis, infective endocarditis, pneumonia, bacteremia and acute appendicitis. [13][14][15][16][17] In our study, we found that lymphocyte was higher in the patient group than the control group, and as a result, NLR was significant. This result supports the cause of chronic inflammation which plays an etiologic role in children with LAP.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, NLR has been recognized as a simple and cost-effective peripheral biomarker that indicates the inflammatory status because it is believed to reflect the numerical balance between neutrophils and lymphocytes in the blood (9,10,15,16). CRP and ESR are elevated in the event of systemic inflammation, and combined use of ESR and CRP was considered to be more appropriate as inflammatory markers (17).…”
Section: Discussionmentioning
confidence: 99%